A feasibility study on the eNAI system - Ibaviosa, Raphael Dominic; Lafavilla, Marc Argie P.; San Buenaventura, Niezl Angela; Villamala, Kyra Louise
The objective of this study is to evaluate if eNAI: Electronic Natal Assistive Intervention device is a feasible venture. eNAI is a device that monitors the progress of labor. The eNAI device has: medical sensors that monitors the delivering mother's vital signs, a tele-referral function that enables remote consultation with 08/GYN, and has a built-in medical recording system. This paper is divided into four parts: market, technical, financial, and socio-profitability analyses. In the market feasibility, the impact and usefulness of eNAI in maternal health in the Philippines is characterized. This enabled the group to assess the need for eNAI in the basic health care system in the Philippines. The group then identified the potential market of eNAI and assessed its 5-year sales projection in terms of product and service revenue. Marketing mix was devised to suit the different sectors eNAI will cater. In the technical feasibility, the requirements in operating the eNAI system: both in the production and service facilities were identified. The pre-capital expenditure, fixed investment cost, operating costs were also determined. Finally, the business-start up cost was computed to be Php 13,586,000. In the financial analysis, the sources of financing the business start-up cost were evaluated. The breakdown for financing is as follow: 40% from bank loan, 35% from angel investors, and 25% from the business proponents. This part is crucial since it also determines if the project is worthy of investment. As for the business, the computed IRR was 19.45% which is greater than the 15% MARR. The last part is determining the ratio between the monetary benefits of the eNAI system in terms of its potential socio-economic contributions versus the total costs of setting up the system. Overall, the eNAI system was found to be feasible.